Mefloquine pharmacokinetics and mefloquine-artesunate effectiveness in Peruvian patients with uncomplicated Plasmodium falciparum malaria - Gutman, Julie (BioMed Central, 2009)
BACKGROUND: Artemisinin-based combination therapy (ACT) is recommended as a means of prolonging the effectiveness of first-line malaria treatment regimens. Different brands of mefloquine (MQ) have been reported to be non-bioequivalent; this could result in sub-therapeutic levels of mefloquine with decreased efficacy. In 2002, mefloquine-artesunate (MQ-AS) combination therapy was adopted as the first-line treatment for uncomplicated Plasmodium falciparum malaria in the Amazon region of Peru. Although MQ resistance has yet to be reported from the Peruvian Amazon, it has been reported from other countries in the Amazon Region. Therefore, continuous monitoring is warranted to ensure that the first-line therapy remains efficacious. This study examines the in vivo efficacy and pharmacokinetic parameters through Day 56 of three commercial formulations of MQ (Lariam(®), Mephaquin(®), and Mefloquina-AC(® )Farma) given in combination with artesunate. METHODS: Thirty-nine non-pregnant adults with P. falciparum mono-infection were randomly assigned to receive artesunate in combination with either (1) Lariam, (2) Mephaquin, or (3) Mefloquina AC. Patients were assessed on Day 0 (with blood samples for pharmacokinetics at 0, 2, 4, and 8 hours), 1, 2, 3, 7, and then weekly until day 56. Clinical and parasitological outcomes were based on the standardized WHO protocol. Whole blood mefloquine concentrations were determined by high-performance liquid chromatography and pharmacokinetic parameters were determined using non-compartmental analysis of concentration versus time data. RESULTS: By day 3, all patients had cleared parasitaemia except for one patient in the AC Farma arm; this patient cleared by day 4. No recurrences of parasitaemia were seen in any of the 34 patients. All three MQ formulations had a terminal half-life of 14–15 days and time to maximum plasma concentration of 45–52 hours. The maximal concentration (C(max)) and interquartile range was 2,820 ng/ml (2,614–3,108) for Lariam, 2,500 ng/ml (2,363–2,713) for Mephaquin, and 2,750 ng/ml (2,550–3,000) for Mefloquina AC Farma. The pharmacokinetics of the three formulations were generally similar, with the exception of the C(max )of Mephaquin which was significantly different to that of Lariam (p = 0.04). CONCLUSION: All three formulations had similar pharmacokinetics; in addition, the pharmacokinetics seen in this Peruvian population were similar to reports from other ethnic groups. All patients rapidly cleared their parasitaemia with no evidence of recrudescence by Day 56. Continued surveillance is needed to ensure that patients continue to receive optimal therapy.